Centralising Dynamics in Australian Federalism - Fenna, Alan (University of Queensland and Blackwell Publishing Asia, 2012)
The steady centralisation that is generally held to be a characteristic feature of Australian federalism has occasioned thorough description and regular comment but much less attempt at explanation or theorisation. This paper reviews the way we account for centralisation in federal systems in general and Australian federalism in particular. In doing so, it considers institutional and societal modes of explanation in the context of patterns of difference between the leading federations. It concludes that as far as those broader patterns, or secular trends, are concerned, there is no avoiding a societal explanation — one that highlights the balance between forces of modernisation and the existence of a “federal society”.